An Elastic Optical Network-based Architecture for the 5G Fronthaul - Riva, Mateus; Donâncio, Henrique; Almeida, Felipe R.; Figueiredo, Gustavo B.; Tinini, Rodrigo I.; Cesar Jr., Roberto M.; Batista, Daniel M. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2018: Anais do XXXVI Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2018)
In 5G networks, the traffic demands are expected to increase significantly. To deal with this problem, many research efforts focus on TWDMPON for the fronthaul. However, TWDM-PON suffers from the issue of wasted bandwidth when a demand is smaller than the channel. In order to avoid this inefficiency, we propose an OFDM-PON supported architecture for the Cloud Radio Access Network (C-RAN) topology to implement the technology of elastic optical networks into C-RAN. Experiments show that OFDM-PON allows for improved usage of the bandwidth (between 145% and 218% improvement), similar average wait time for requests (average difference below 7%), and similar request loss (average difference below 2%) in comparison to TWDM.